Analisis Faktor Etika, Budaya Birokrasi, Tekanan Sosial dan Kapasitas Individu terhadap Budgetary Slack (Senjangan Anggaran) (Kajian Perilaku Eksekutif Dalam Proses Penyusunan Anggaran Di Badan Koordinator Wilayah II Jawa Timur) - Maskun, Ali (Universitas Brawijaya, Indonesia, 2009)
Budgetary Slack is the between estimated budget and its realization (Ueno & Sekaran 1990). In arranging revenue budget, there is predisposition to underestimate the revenue, while, contrastingly, in arranging expenditure budget, the predisposition is to overestimate the expenditure. Budget tolerance is ranging between 5% and 10 %. Both the executive and legislative have different interest on the APBD as the joint product of those institutions. Executive's achievement is evaluated based on APBD realization and its accountability to the legislative. This study was aimed to prove that ethics, bureaucratic culture (in this case, the paternalistic culture), social pressure and individual capacity have influence on budgetary slack among the budgeting executives in Area Coordinating Board II East Java. This study was conducted in Regional Government in Area Coordinating Board II East Java, including the Districts of Bojonegoro, Tuban, Lamongan, Mojokerto, Jombang, Kediri, and the cities of Kediri and Mojokerto. Samples were taken in purposive sampling with total respondents of 236 individuals of the echelon II and III. Variables involved were ethics, bureaucratic culture (in this case, the paternalistic culture), social pressure, individual capacity and budgetary slack. Data were analyzed using Structural Equation Modeling (SEM) analysis. Result of this study proved that ethics have positive and significant effect on budgetary slack among the budgeting executives, bureaucratic culture have negative and significant effect on budgetary slack among the budgeting executives, social pressure have positive and significant influence on the budgetary slack among budgeting executives, and individual capacity had no influence on the budgetary slack among budgeting executives.